Composite positive electrode and preparation method thereof, and all-solid-state battery

CN123017874APending Publication Date: 2026-10-30SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611192669.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

界面接触差、阻抗高:LRMO与无机固态电解质(如硫化物)物理/化学相容性差,导致界面接触不良,产生高界面阻抗,严重限制锂离子传输动力学;

Benefits of technology

(1)体相-界面梯度高价阳离子掺杂

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion battery production and relates to a composite positive electrode, a preparation method thereof and a full-solid-state battery. 5 The composite positive electrode comprises a lithium-rich manganese-based positive electrode material doped with Ta The application adjusts and controls the surface structure of a lithium-rich manganese-based positive electrode material (LRMO) through a multifunctional interface engineering to construct an efficient and stable lithium ion / electron transport channel, inhibit oxygen precipitation and relieve voltage attenuation, so that the cycle stability and rate performance of the lithium-rich manganese-based positive electrode material in a full-solid-state battery are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery production technology, and in particular to a composite cathode and its preparation method, and an all-solid-state battery. Background Technology

[0002] All-solid-state batteries are lithium-ion batteries that use solid-state electrolytes instead of liquid electrolytes. Due to their advantages such as high safety performance, high energy density, and wide operating temperature range, all-solid-state batteries have broad application prospects, such as new energy vehicles, energy storage systems, and consumer electronics. They have become a research hotspot in the field of lithium-ion batteries and have attracted much attention.

[0003] Lithium-rich manganese-based cathode materials (such as XLi2MnO3·(1−x)LiMO2) are considered ideal cathodes for high-energy-density batteries due to their high specific capacity (>250 mAh / g). However, their application in all-solid-state lithium batteries faces the following key bottlenecks: Poor interfacial contact and high impedance: LRMO has poor physical / chemical compatibility with inorganic solid electrolytes (such as sulfides), resulting in poor interfacial contact and high interfacial impedance, which severely limits lithium-ion transport kinetics. Surface oxygen is unstable: when the charging voltage is higher than 4.5V (vs. Li⁺ / Li), lattice oxygen is easily oxidized and released (O₂). 2- →O2↑), triggering an irreversible phase transition (layered → spinel / rock salt phase), resulting in continuous voltage decay; high lithium-ion migration barrier, lack of continuous ion channels at the solid-solid interface, Li + The high activation energy for migration at the interface (typically above 0.4 eV) results in poor rate performance.

[0004] The combined effects of these problems lead to rapid capacity decay of the LRMO cathode in all-solid-state batteries after hundreds of cycles, making it difficult to meet the requirements of long-life applications (such as electric vehicles and energy storage systems). Existing technologies such as Al2O3 coating and bulk doping can only partially alleviate individual problems and cannot simultaneously optimize ion / electron transport and stabilize the oxygen framework. Therefore, an integrated and multifunctional interface control method is urgently needed. Summary of the Invention

[0005] To address the aforementioned problems, this invention discloses a composite cathode and its preparation method, as well as an all-solid-state battery. The technical solution of this invention is implemented as follows: The first aspect of this invention discloses a composite positive electrode comprising Ta 5 ⁺ Doped lithium-rich manganese-based cathode material, first sulfide solid electrolyte, conductive polymer and fluoride.

[0006] Furthermore, the first sulfide solid electrolyte includes Li6PS5Cl and Li7P3S. 11At least one of Li6PS5Br.

[0007] Furthermore, the conductive polymer includes at least one of polypyrrole, poly3,4-ethylenedioxythiophene, polyaniline, polythiophene, poly(3-methylthiophene), polyindole, and polycarbazole.

[0008] Furthermore, the fluoride is a lithium-containing fluoride.

[0009] Furthermore, the Ta 5+ In doped lithium-rich manganese-based cathode materials, Ta 5+ Ta exhibits a gradient distribution within the grains, with the surface layer... 5+ Concentration higher than internal Ta 5+ concentration.

[0010] The second aspect of this invention discloses a method for preparing a composite positive electrode, the method being used to prepare the composite positive electrode disclosed in the first aspect of this invention, the method comprising the following steps: S1. A lithium source, a manganese source, an M source, and a tantalum source are mixed and calcined in two stages to obtain a first intermediate; the M source is a mixture of a nickel source and a cobalt source. S2. The first intermediate, the first sulfide solid electrolyte, the conductive polymer precursor and the fluorine source prepared in step S1 are mixed and then polymerized and heat-treated to obtain the second intermediate. S3. The second intermediate, the second sulfide solid electrolyte, the conductive agent, and the binder prepared in step S2 are mixed to form a slurry, which is then coated onto the positive electrode current collector and dried to obtain a composite positive electrode.

[0011] Furthermore, in step S1, in the first intermediate, based on the total amount of transition metals, Ta 5+ The addition amount is 0.5 mol%~1.2 mol%.

[0012] Furthermore, the tantalum source mentioned in step S1 includes at least one of tantalum pentoxide, tantalum oxalate, tantalum ethoxide, tantalum chloride, and lithium tantalate.

[0013] Furthermore, in step S1, the first stage of calcination is at a temperature of 820~860℃, and the second stage is at a temperature of 880~930℃.

[0014] Furthermore, in step S2, based on the total mass of the first intermediate, the first sulfide solid electrolyte, the conductive polymer precursor, and the fluorine source being 100%, the mass percentage of the first intermediate is 87%-92%; the mass percentage of the first sulfide solid electrolyte is 5%-9%; the mass percentage of the conductive polymer precursor is 1.2%-2.8%; and the mass percentage of the fluorine source is 0.5%-1.5%.

[0015] Furthermore, the polymerization temperature in step S2 is 60~90℃; the heat treatment temperature is 100~150℃.

[0016] The third aspect of the present invention discloses an all-solid-state battery, comprising the composite positive electrode, negative electrode sheet and solid electrolyte membrane disclosed in the first aspect of the present invention.

[0017] The advantages of this invention are as follows: (1) Bulk-interfacial gradient high-valence cation doping Ta 5+ Gradient bulk doping: To address the problems of oxygen instability, severe phase transition, and high ion migration resistance in pure LRMO bulk, this invention introduces gradient doping to strengthen the lattice MO bonds, suppress oxygen vacancy generation from the inside of the lattice, and form a buffer phase on the surface to suppress bulk structure collapse; however, doping alone still results in poor solid-solid interface contact, limited interfacial ion / electron transport, and voltage decay that are not fundamentally solved.

[0018] (2) In-situ construction of Li⁺ continuous conductive interface layer This invention mixes gradient-doped LRMO powder with a first sulfide solid electrolyte to form Li on the particle surface. + A continuous conduction network reduces the migration barrier at the solid-solid interface. However, a simple electrolyte complex has poor electronic conductivity, severe polarization at high rates, and lacks effective suppression of lattice oxygen release under high voltage.

[0019] (3) Introducing conductive polymer precursors to build an electronic network This invention adds a conductive polymer precursor to the aforementioned mixed system, performs low-temperature in-situ polymerization, and applies it to the surface of LRMO particles and Li... + An electronically conductive framework is formed within the conductive network, solving the problem of overall electron conduction at the positive electrode and optimizing rate performance; at this time, Li + The dual continuity of the electron and liquid channels enables a Li⁺ / e⁻ dual-continuous conductive interface layer. However, there is still a high-voltage risk of lattice oxygen deposition at the interface, and the capacity will still slowly decay during long-term cycling.

[0020] (4) Introduce a fluorine source to generate LiF in situ to achieve oxygen anchoring closed loop. This invention introduces a fluorine source into the interface layer to generate nano-lithium fluoride (LiF) in situ, forming strong bonds to anchor lattice oxygen and significantly improving the oxygen evolution barrier. The four-step synergistic approach—bulk phase doping to stabilize the lattice, lithium access via the interface electrolyte, electron access via the polymer, and oxygen locking at the fluorine interface—overcomes the limitations of single-modification methods in existing technologies. Detailed Implementation

[0021] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0022] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used in the detailed description is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having” and any variations thereof in the specification and claims of this invention are intended to cover non-exclusive inclusion.

[0023] In the description of specific embodiments of the present invention, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, "multiple" means two or more, unless otherwise explicitly defined.

[0024] In this invention, the reference to "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this invention can be combined with other embodiments.

[0025] In the description of the embodiments of this invention, the term "and / or" is merely a description of the relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, in this invention, the character " / " generally indicates that the preceding and following associated objects have an "or" relationship.

[0026] Throughout this invention, numerical values ​​represent approximate measures or limits of a range to cover minute deviations from a given value, as well as embodiments with approximately the mentioned value and embodiments with the exact mentioned value. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., quantities or conditions) in this specification (including the appended claims) should be understood to be modified in all cases by the term “about,” regardless of whether “about” actually appears before the numerical value. “About” indicates that the stated numerical value allows for some minor inaccuracy (approaching the exact value in some way; approximately or reasonably approaching the value; almost). If the inaccuracy provided by “about” is not otherwise understood in this general sense in the art, then “about” as used in this invention at least indicates a variation that can be produced by common methods of measuring and using such a parameter. For example, “about” may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some respects, optionally less than or equal to 0.1%.

[0027] Additionally, the disclosure of the range includes the disclosure of all values ​​across the entire range and the disclosure of further subdivided ranges, including the endpoints and subranges given for these ranges.

[0028] To overcome the limitations of existing technologies where single modification (such as Al2O3 coating or bulk doping) cannot simultaneously optimize ion / electron transport and stabilize the oxygen framework, this invention modulates the surface structure of lithium-rich manganese-based cathode material (LRMO) through multifunctional interface engineering to construct efficient and stable lithium-ion / electron transport channels, suppress oxygen evolution, and alleviate voltage decay, thereby significantly improving its cycle stability and rate performance in all-solid-state batteries.

[0029] The first aspect of this invention discloses a composite positive electrode comprising Ta 5 ⁺ Doped lithium-rich manganese-based cathode material, first sulfide solid electrolyte, conductive polymer and fluoride.

[0030] Ta 5+ The ionic radius has a higher compatibility with the LRMO lattice, enabling bulk-interface gradient doping with enrichment in the outer layer and moderate doping in the inner layer, without disrupting the lithium storage sites in the main lattice. Then, LRMO powder is mixed with a first sulfide solid electrolyte to form Li on the particle surface. + A continuous conductive network is used to reduce the solid-solid interface migration barrier. Then, a conductive polymer precursor is added, followed by low-temperature in-situ polymerization, to achieve this on the surface of LRMO particles and Li. + An electronically conductive framework is formed within the conductive network, solving the problem of overall electron conduction at the positive electrode and optimizing rate performance; at this time, Li +The dual continuity of the channel and the electron channel realizes the Li⁺ / e⁻ dual continuous conductive interface layer. Finally, a fluorine source is introduced into the interface layer to generate nano-LiF in situ, forming strong bonds to anchor lattice oxygen and significantly improving the oxygen evolution energy barrier.

[0031] In some embodiments, the first sulfide solid electrolyte includes Li6PS5Cl and Li7P3S. 11 At least one of Li6PS5Br.

[0032] In some embodiments, the conductive polymer includes at least one of polypyrrole, poly3,4-ethylenedioxythiophene, polyaniline, polythiophene, poly(3-methylthiophene), polyindole, and polycarbazole.

[0033] In some embodiments, the fluoride is a lithium-containing fluoride.

[0034] In this invention, "at least one" means that one element can be selected from the listed elements as the technical solution, or a mixture of two or more elements can be selected as the technical solution. Since the listed elements have similar physicochemical properties, do not react with each other, and play similar roles in the mixture system, this invention does not limit the use of the above-mentioned alternative or combined forms. The same applies below.

[0035] In some implementations, Ta 5+ In doped lithium-rich manganese-based cathode materials, Ta 5+ Ta exhibits a gradient distribution within the grains, with the surface layer... 5+ Concentration higher than internal Ta 5+ concentration.

[0036] The second aspect of this invention discloses a method for preparing a composite positive electrode, the method being used to prepare the composite positive electrode disclosed in the first aspect of this invention, the method comprising the following steps: S1. A lithium source, a manganese source, an M source, and a tantalum source are mixed and calcined in two stages to obtain a first intermediate; the M source is a mixture of a nickel source and a cobalt source. S2. The first intermediate, the first sulfide solid electrolyte, the conductive polymer precursor and the fluorine source prepared in step S1 are mixed and then polymerized and heat-treated to obtain the second intermediate. S3. The second intermediate, the second sulfide solid electrolyte, the conductive agent, and the binder prepared in step S2 are mixed to form a slurry, which is then coated onto the positive electrode current collector and dried to obtain a composite positive electrode.

[0037] In some embodiments, step S1 includes mixing a lithium source and a transition metal in a molar ratio of (1.05~1.2):1, then adding 0.5~1.2 mol% of a tantalum source, and stirring at 40℃~60℃ for 2h~5h to obtain an LRMO cathode precursor. For example, the molar ratio of lithium source to transition metal can be selected as 1.05:1, 1.06:1, 1.08:1, 1.1:1, 1.12:1, 1.14:1, 1.15:1, 1.18:1, or 1.2:1.

[0038] The transition metal includes a manganese source and an M source; the M source is a mixture of a nickel source and a cobalt source; the molar ratio of the manganese source to the M source in the transition metal is (0.65~0.9:(0.1~0.35)). For example, the molar ratio of manganese source to M source can be selected as 0.65:0.1, 0.68:0.1, 0.7:0.1, 0.72:0.1, 0.75:0.1, 0.78:0.1, 0.8:0.1, 0.82:0.1, 0.85:0.1, 0.88:0.1, 0.9:0.1, 0.65:0.2, 0.68:0.2, 0.7:0.2, 0.72:0.2, 0.75:0.2, 0.78:0.2, 0.8:0.2, 0.82:0.2, 0.85:0.2, 0.88:0.2, 0.9:0. 0.2, 0.65:0.3, 0.68:0.3, 0.7:0.3, 0.72:0.3, 0.75:0.3, 0.78:0.3, 0.8:0.3, 0.82:0.3, 0.85:0.3, 0.88:0.3, 0.9:0.3, 0.65:0.35, 0.68:0.35, 0.7:0.35, 0.72:0.35, 0.75:0.35, 0.78:0.35, 0.8:0.35, 0.82:0.35, 0.85:0.35, 0.88:0.35, 0.9:0.35, etc.

[0039] In the mixture of transition metal and tantalum source, the molar percentage of tantalum source is 0.5 mol% to 1.2 mol%. For example, the molar percentage of tantalum source can be selected as 0.5 mol%, 0.6 mol%, 0.7 mol%, 0.8 mol%, 0.9 mol%, 1 mol%, 1.1 mol%, 1.2 mol%, etc.

[0040] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate, and lithium iodide.

[0041] In some embodiments, the manganese source includes at least one of manganese carbonate, manganese dioxide, manganese monoxide, metallic manganese, manganese nitrate, manganese acetate, manganese oxalate, manganese sulfate, manganese chloride, and manganese phosphate.

[0042] In some embodiments, the nickel source includes at least one of nickel oxide, nickel carbonate, metallic nickel, nickel suboxide, nickel trioxide, nickel hydroxide, nickel nitrate, nickel sulfate, and nickel acetate.

[0043] In some embodiments, the cobalt source includes at least one of cobalt tetroxide, cobalt carbonate, metallic cobalt, cobalt suboxide, cobalt hydroxide, cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt oxalate, cobalt chloride, cobalt(hexa)ammonium salt, and organocobalt compounds.

[0044] In some embodiments, the tantalum source includes at least one of tantalum pentoxide, tantalum oxalate, tantalum ethoxide, tantalum chloride, and lithium tantalate.

[0045] In some embodiments, the first stage of calcination in step S1 involves placing the LRMO cathode precursor in an environment of 820°C to 860°C and holding it in air for 4 to 6 hours. This step is used for the initial formation of the precursor lattice and initial penetration into the grain interior, avoiding element agglomeration caused by high-temperature and rapid sintering. The second stage of calcination involves raising the temperature to 880°C to 930°C and continuing to hold it in air for 8 to 12 hours to obtain Ta. 5 ⁺ Gradient-doped LRMO cathode precursor; this step is used to drive tantalum to be gradient-enriched to the grain surface in the high-temperature section, forming a doping distribution with low inner and high outer doping; at the same time, it improves the crystallinity of the lattice, strengthens the surface bond, and generates an ultra-thin spinel buffer layer in situ. For example, the first stage calcination temperature can be selected as 820℃, 830℃, 840℃, 850℃, 860℃, etc., and the time can be selected as 4h, 4.5h, 5h, 5.5h, 6h, etc.; the second stage calcination temperature can be selected as 880℃, 890℃, 900℃, 910℃, 920℃, 930℃, etc., and the time can be selected as 8h, 9h, 10h, 11h, 12h, etc.

[0046] In some embodiments, the conductive polymer precursor in step S2 includes at least one of pyrrole monomer, 3,4-ethylenedioxythiophene monomer, aniline monomer, thiophene monomer, 3-methylthiophene, indole monomer, and carbazole monomer.

[0047] In some embodiments, the fluorine source in step S2 is selected from at least one of ammonium fluoride, fluorinated polyethylene, fluoroboric acid, and ammonium fluoride complex.

[0048] In some embodiments, based on the total mass of the first intermediate, the first sulfide solid electrolyte, the conductive polymer precursor, and the fluorine source prepared in step S1 as 100%, the mass percentage of the first intermediate is 87%-92%; the mass percentage of the first sulfide solid electrolyte is 5%-9%; the mass percentage of the conductive polymer precursor is 1.2%-2.8%; and the mass percentage of the fluorine source is 0.5%-1.5%.

[0049] For example, the mass percentage of the first intermediate can be selected as 87%, 88%, 89%, 90%, 91%, 92%, etc.; the mass percentage of the first sulfide solid electrolyte can be selected as 5%, 6%, 7%, 8%, 9%, etc.; the mass percentage of the conductive polymer precursor can be selected as 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 2.0%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.8%, etc.; and the mass percentage of the fluorine source can be selected as 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.3%, 1.4%, 1.5%, etc.

[0050] In some embodiments, the first intermediate, the first sulfide solid electrolyte, the conductive polymer precursor and the fluorine source prepared in step S1 are mixed and ball-milled for 6-8 hours; polymerized at 60°C-90°C for 1-3 hours; and heat-treated at 100°C-150°C for 3-5 hours to obtain the interface-controlled LRMO cathode material.

[0051] For example, the ball milling time can be selected as 6h, 6.5h, 7h, 7.5h, 8h, etc.; the polymerization temperature can be selected as 60°C, 70°C, 80°C, 90°C, etc.; the polymerization time can be selected as 1h, 1.5h, 2h, 2.5h, 3h, etc.; the heat treatment temperature can be selected as 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc.; and the heat treatment time can be selected as 3h, 3.5h, 4h, 4.5h, 5h, etc.

[0052] This in-situ polymerization process forms a composite interface layer with a thickness of 5 nm-20 nm on the surface of LRMO particles without affecting the structure of the first sulfide electrolyte. For example, the thickness of the composite interface layer can be selected from 5 nm, 6 nm, 8 nm, 9 nm, 10 nm, 12 nm, 15 nm, 16 nm, 18 nm, 19 nm, 20 nm, etc.

[0053] In some embodiments, the conductive agent of the composite positive electrode includes carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.

[0054] In some embodiments, the binder for the positive electrode includes polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0055] In some embodiments, the second sulfide solid electrolyte comprises sulfide solid electrolyte particles and may include one or more sulfide-based materials selected from the group consisting of: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge, and Sn and 0 ≤ x ≤ 2), Li 24.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.24 Li 9.6 P 24 S 12 Li7P 24 S 11 Li9P 24 S9O 24 Li 10.245 Si 1.245 P 1.65 S 12 Li 9.81 Sn 0.81 P 2.19 S 12 Li 10 (Si 0.5 Ge 0.5 P2S 12 Li (Ge 0.5 Sn 0.5 P2S 12 Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br, or I), Li7P2S8I, Li 10.245 Ge 1.245 P 1.65 S 12 Li 24.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 Li 10 SiP2S 12 Li 9.54 Si1.74 P 1.44 S 11.7 Cl 0.24 (1-x)P₂S₅-xLi₂S (where 0.5 ≤ x ≤ 0.7) and combinations thereof. In one variant, one or more sulfide-based materials may have a content greater than or equal to about 10 -7 Ionic conductivity from S / cm to less than or equal to about 1 S / cm.

[0056] The third aspect of the present invention discloses an all-solid-state battery, comprising the composite positive electrode, negative electrode sheet and solid electrolyte membrane disclosed in the first aspect of the present invention.

[0057] The fourth aspect of this invention discloses a method for preparing an all-solid-state battery, used to prepare the all-solid-state battery disclosed in the third aspect of this invention, the method comprising the following steps: A composite positive electrode, a sulfide solid electrolyte membrane, and a negative electrode are sequentially stacked, dry-encapsulated, and then cold-pressed to densify under a pressure of 250 MPa to obtain an all-solid-state battery.

[0058] The present invention also discloses an electrical device, which includes the all-solid-state battery disclosed in the third aspect of the present invention.

[0059] The electrical device described in this application is not particularly limited and can be applied to any electrical device known in the prior art. For example, the electrical device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, household large-capacity batteries, and lithium-ion capacitors.

[0060] To better understand the above-mentioned objectives, features, and advantages of this application, the solutions of this application will be further described below through embodiments and comparative examples. Obviously, the embodiments in this specification are only one embodiment of the present invention, and not all embodiments.

[0061] Example 1: An all-solid-state battery, the preparation process of which is as follows: Preparation of composite cathode: Preparation of the first intermediate: Lithium source (lithium carbonate), manganese source (manganese dioxide), nickel source (nickel oxide), and cobalt source (cobalt tetroxide) were mixed in a molar ratio of 1.1:0.68:0.17:0.15; stirred at 50°C for 3.5 h; precursor was synthesized; 0.8 mol% tantalum source tantalum pentoxide was added (based on the total molar amount of transition metals, blended during the synthesis stage); where transition metals refer to the mixture of manganese, nickel, and cobalt sources; 2. Gradient calcination: sintering is performed in two stages, first at 850℃ for 5 hours, then at 900℃ for 10 hours to obtain Ta. 5+ Gradient-doped 0.4Li₂MnO₃·0.6Li(M 0.2 Ta 0.8 O2 is the first intermediate.

[0062] 3. The first intermediate, the first sulfide solid electrolyte Li6PS5Cl, the conductive polymer precursor pyrrole monomer and the fluorine source NH4F were ball-milled and mixed at a mass ratio of 90:7:2:1 for 5 hours, then polymerized at 60°C for 2 hours, and finally heat-treated at 150°C for 1 hour to obtain the second intermediate.

[0063] 4. Mix the second intermediate, the second sulfide solid electrolyte Li6PS5Cl, the conductive agent Super P, and the binder PVDF in a mass ratio of 88:9:2:1 until homogeneous. Then add the solvent N-methylpyrrolidone (NMP) and mix to form a positive electrode slurry. Coat the positive electrode slurry onto the positive electrode current collector to form a positive electrode active material layer. After drying, a composite positive electrode is obtained.

[0064] Fabrication of all-solid-state batteries: Solid electrolyte membrane preparation: 95% sulfide electrolyte Li6PS5Cl was used, supplemented with 5 wt% binder PTFE, dry film formation / wet coating, with a thickness of 50 μm; Negative electrode (Li-In alloy): Li-In alloy negative electrode is selected, with In content of 10 wt% and alloy foil thickness of 25 μm; The prepared composite positive electrode, sulfide solid electrolyte membrane, and Li-In alloy negative electrode are stacked sequentially, dry-encapsulated, and cold-pressed to densify (pressure 250 MPa) to complete the assembly of an all-solid-state single cell.

[0065] Example 2: An all-solid-state battery, the preparation method of which is basically the same as that of Example 1, the only difference being that: in this example, the first sulfide solid electrolyte in the composite cathode is Li7P3S. 11 The conductive precursor is aniline monomer; the fluorine source is ammonium fluoride.

[0066] Example 3: An all-solid-state battery, the preparation method of which is basically the same as that of Example 1, the only difference being that in this example, the mass ratio of the first intermediate, the first sulfide solid electrolyte Li6PS5Cl, the conductive polymer precursor pyrrole monomer and the fluorine source NH4F in the composite cathode is 89:7.5:2:1.5.

[0067] Example 4: An all-solid-state battery, the preparation method of which is basically the same as that of Example 1, the only difference being that in this example, the mass ratio of the first intermediate, the first sulfide solid electrolyte Li6PS5Cl, the conductive polymer precursor pyrrole monomer and the fluorine source NH4F in the composite cathode is 92:5:2:1.

[0068] Example 5: An all-solid-state battery, the preparation method of which is basically the same as that of Example 1, the only difference being that in this example, the mass ratio of the first intermediate, the first sulfide solid electrolyte Li6PS5Cl, the conductive polymer precursor pyrrole monomer and the fluorine source NH4F in the composite cathode is 94:3:2:1.

[0069] Example 6: An all-solid-state battery, the preparation method of which is basically the same as that of Example 1, the only difference being that in this example, the mass ratio of the first intermediate, the first sulfide solid electrolyte Li6PS5Cl, the conductive polymer precursor pyrrole monomer and the fluorine source NH4F in the composite cathode is 86:11:2:1.

[0070] Comparative Example 1: An all-solid-state battery, the preparation method of which is basically the same as that of Example 1, except that: in this comparative example, the first sulfide solid electrolyte, conductive polymer precursor and fluorine source are not added, and the remaining components (conductive agent, binder, etc.) are the same as those in Example 1.

[0071] Comparative Example 2: An all-solid-state battery, the preparation method of which is basically the same as that of Example 1, the only difference being that: in this comparative example, no first sulfide solid electrolyte is added to the composite cathode.

[0072] In the composite cathode, the mass ratio of the first intermediate, the conductive polymer precursor pyrrole monomer, and the fluorine source NH4F is 97:2:1.

[0073] Comparative Example 3: An all-solid-state battery, whose preparation method is basically the same as that of Example 1, except that the preparation process of the second intermediate in this comparative example is as follows: The first intermediate, the first sulfide solid electrolyte Li6PS5Cl, and the fluorine source NH4F were ball-milled and mixed at a mass ratio of 92:7:1 for 5 hours, then polymerized at 60°C for 2 hours, and finally heat-treated at 150°C for 1 hour to obtain the second intermediate.

[0074] Comparative Example 4: An all-solid-state battery, whose preparation method is basically the same as that of Example 1, except that the preparation process of the second intermediate in this comparative example is as follows: The first intermediate, the first sulfide solid electrolyte Li6PS5Cl, and the conductive polymer precursor pyrrole monomer were ball-milled and mixed at a mass ratio of 91:7:2 for 5 hours, then polymerized at 60°C for 2 hours, and finally heat-treated at 150°C for 1 hour to obtain the second intermediate.

[0075] Comparative experiment: Ten sets of samples (20 samples in each set) were taken from Examples 1-6 and Comparative Examples 1-4, and the following tests were performed on them respectively.

[0076] 1. 1C discharge capacity test: At room temperature (25 °C), with a voltage range of 2.0–4.8 V, constant current charge and discharge at 1 C, after the first formation cycle, the discharge capacity of the second cycle is recorded.

[0077] 2. Average voltage decay rate (first 500 cycles) test: Test method: 1C cyclic charge and discharge, record the median discharge voltage every 50 cycles, calculate the overall voltage linear decay slope over 500 cycles, and obtain the average voltage decay rate per cycle.

[0078] 3. Capacity retention test after 2000 cycles: Test method: long cycle at room temperature and 1C. Based on the stable discharge capacity of the first cycle, calculate the remaining capacity after 2000 cycles / the capacity of the first cycle × 100%.

[0079] 3. Interfacial impedance testing: Electrochemical workstation, frequency range 10⁻²~10 6 Hz, perturbation amplitude 5mV, fit solid-solid interface charge transfer impedance Rct.

[0080] 4. Li + Activation energy of migration test: variable temperature EIS test (25℃~60℃), the impedance-temperature relationship was fitted according to the Arrhenius formula, and Li was calculated. + Interface migration activation energy.

[0081]

[0082] As shown in the table above, Example 1 (four-component synergy) exhibits the best overall performance: a 1C discharge capacity of 245 mAh / g, a capacity retention of 82% after 2000 cycles, an interfacial impedance of only 0.78 Ω·cm², a Li⁺ migration activation energy as low as 0.32 eV, and an average voltage decay rate of only 0.3 mV / cycle. In contrast, Comparative Example 1 (Ta only) 5The capacity of the Li⁺-doped sample was as low as 215 mAh / g, with a doubled voltage decay rate. Comparative Example 2 (sulfide-deficient electrolyte) showed an increased interfacial impedance of 0.95 Ω·cm². Comparative Example 3 (conductive polymer-deficient) exhibited a dramatic increase in interfacial impedance to 1.25 Ω·cm², with a capacity reduced to 225 mAh / g. Comparative Example 4 (fluorine-deficient source) showed a voltage decay rate as high as 0.85 mV / cycle, with a Li⁺ migration activation energy of 0.65 eV. Examples 2-4 maintained good performance even after component substitution or ratio adjustment, while Examples 5-6 showed a decrease in performance due to exceeding the preferred range (too high LRMO or too low / too high first sulfide), further confirming the synergistic optimization effect of the various substances in the composite cathode disclosed in this invention.

[0083] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A composite positive electrode, characterized in that, Including Ta 5 ⁺ Doped lithium-rich manganese-based cathode material, first sulfide solid electrolyte, conductive polymer and fluoride.

2. The composite positive electrode according to claim 1, characterized in that, The first sulfide solid electrolyte includes Li6PS5Cl and Li7P3S 11 The conductive polymer comprises at least one of Li6PS5Br; the conductive polymer comprises at least one of polypyrrole, poly3,4-ethylenedioxythiophene, polyaniline, polythiophene, poly(3-methylthiophene), polyindole, and polycarbazole; the fluoride is a lithium-containing fluoride.

3. The composite positive electrode according to claim 1, characterized in that, The Ta 5+ In doped lithium-rich manganese-based cathode materials, Ta 5+ Ta exhibits a gradient distribution within the grains, with the surface layer... 5+ Concentration higher than internal Ta 5+ concentration.

4. A method for preparing a composite positive electrode as described in any one of claims 1-3, characterized in that, The steps include the following: S1. A lithium source, a manganese source, an M source, and a tantalum source are mixed and calcined in two stages to obtain a first intermediate; the M source is a mixture of a nickel source and a cobalt source. S2. The first intermediate, the first sulfide solid electrolyte, the conductive polymer precursor and the fluorine source prepared in step S1 are mixed and then polymerized and heat-treated to obtain the second intermediate. S3. The second intermediate, the second sulfide solid electrolyte, the conductive agent, and the binder prepared in step S2 are mixed to form a slurry, which is then coated onto the positive electrode current collector and dried to obtain a composite positive electrode.

5. The method according to claim 4, characterized in that, In step S1, in the first intermediate, based on the total amount of transition metals, Ta 5+ The addition amount is 0.5 mol%~1.2 mol%.

6. The method according to claim 4, characterized in that, The tantalum source mentioned in step S1 includes at least one of tantalum pentoxide, tantalum oxalate, tantalum ethoxide, tantalum chloride, and lithium tantalate.

7. The method according to claim 4, characterized in that, In step S1, the first stage of calcination is carried out at a temperature of 820~860℃, and the second stage is carried out at a temperature of 880~930℃.

8. The method according to claim 4, characterized in that, In step S2, based on the total mass of the first intermediate, the first sulfide solid electrolyte, the conductive polymer precursor, and the fluorine source being 100%, the mass percentage of the first intermediate is 87%-92%; the mass percentage of the first sulfide solid electrolyte is 5%-9%; the mass percentage of the conductive polymer precursor is 1.2%-2.8%; and the mass percentage of the fluorine source is 0.5%-1.5%.

9. The method according to claim 4, characterized in that, The polymerization temperature in step S2 is 60~90℃; the heat treatment temperature is 100~150℃.

10. An all-solid-state battery, characterized in that, It includes a positive electrode, a solid electrolyte membrane, and a negative electrode, wherein the positive electrode includes a composite positive electrode as described in any one of claims 1 to 3.